Boys & sex : young men on hookups, love, porn, consent, and navigating the new masculinity - Orenstein, Peggy (Harper, an Imprint of HarperCollins Publishers, 2020)
"Peggy Orenstein's Girls & Sex broke ground, shattered taboos, and galvanized conversations about young women's right to pleasure and agency in sexual encounters. It also had an unintended effect on its author: Orenstein realized that talking about girls is only half the conversation. To understand girls and sex, we also need to talk about boys and sex. Today's young men are subject to the same cultural forces as their female peers. They are steeped in the distorted media images and binary stereotypes of female sexiness and toxic masculinity which shape how they, too, navigate sexual and emotional relationships. In Boys & Sex, Orenstein uses the same fascinating mix of anecdote and research to reveal how young men understand and negotiate the new rules of physical and emotional intimacy. Drawing on comprehensive interviews with young men, psychologists, academics, and experts in the field, Orenstein takes an unprecedented look at the myriad factors that are shaping boys' ideas of sex, girls, and masculinity including: locker room talk, how the word "hilarious" robs boys of empathy, pornography as the new sex education, hookup culture and consent, Bro culture and #metoo, excessive drinking and frat parties boys' experience as victims and perpetrators of sexual violence. By exploring the complexity of young men's attitudes, beliefs, and experiences, Orenstein unravels the hidden truths, hard lessons, and important realities of boys' sex lives today. The result is a provocative and paradigm-shifting work that offers a much-needed vision of how boys can truly move forward as better men"--